TINGKAT PENGUASAAN TATA BAHASA BAKU BAHASA INDONESIA OLEH GURU BAHASA INDONESIA SMA DI KABUPATEN LAMONGAN - Markub Markub; Laila Tri Lestari (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The general objective of this study is to describe the level of mastery of grammar Baku Indonesian by Indonesian teacher from high school in Lamongan andrank the most difficult grammar for Indonesian teachers in Lamongan. This study was designed in a quantitative descriptive study. The source of research data is a teacher Indonesian high school in Lamongan. Analyzing data is performed quantitative research. The results showed that the level of mastery TBBBI by Indonesian high school teachers were moderate with a mean score of 63. Rating grammatical difficulties for Indonesian teachers the highest high school is the syntax (score 60), followed by successive order of words (score 64) and sound system (score 66).